Vitamin D supplementation differentially affects seasonal multiple sclerosis disease activity. Issue 8 (11th July 2017) - Miclea, Andrei; Miclea, Marius; Pistor, Maximilian; Hoepner, Andreas; Chan, Andrew; Hoepner, Robert
Abstract: Objectives: Low ultraviolet‐B (UVB) radiation causes hypovitaminosis D, which is a known risk factor for multiple sclerosis (MS) and associated with MS disease activity. Our objective is to test whether vitamin D supplementation is most effective in lowering disease activity during the period of the year with low UVB radiation and consequently low serum 25‐hydroxyvitamin D3 (25(OH)D3 ) concentration. Methods: Retrospective analysis of medical records from our outpatient department identified 40 MS patients with available data of at least 6 months before and during oral vitamin D supplementation. Serum 25(OH)D3 concentration was analyzed using immunoassay. UVB radiation data were provided by the local government. Annualized and quarterly relapse rates before and during vitamin D supplementation served as outcome parameters. Results: During vitamin D supplementation (18, 950 international units/week (mean, SD 3, 397)), serum 25(OH)D3 concentration increased by 51 nmol/L and the UVB‐related seasonal variability in 25(OH)D3 levels ceased (rho = −0.13, p > .05). Furthermore, the annualized relapse rate decreased by approximately 50%. This was almost solely driven by the prominent reduction in the quarterly relapse rate in late winter/early spring, when 25(OH)D3 levels of nonsupplemented patients were the lowest. Conclusions: Our study demonstrated the modulation of seasonal MS disease activity through vitamin D supplementation. Given the prominent reduction in the quarterly relapse rate in late winter/early spring, our data indicate a beneficial effect of supplementing MS patients with vitamin D, especially during this period of the year. Abstract : Our study ( n = 40) demonstrated the modulation of seasonal MS disease activity through vitamin D supplementation. Given the prominent reduction in the quarterly relapse rate in late winter/early spring, our data indicate a beneficial effect of supplementing MS patients with vitamin D, especially during this period of the year.